Alternatives to the six-minute walk test in pulmonary arterial hypertension. - Vincent Mainguy (Public Library of Science (PLoS), 2014)
Introduction The physiological response during the endurance shuttle walk test (ESWT), the cycle endurance test (CET) and the incremental shuttle walk test (ISWT) remains unknown in PAH. We tested the hypothesis that endurance tests induce a near-maximal physiological demand comparable to incremental tests. We also hypothesized that differences in respiratory response during exercise would be related to the characteristics of the exercise tests. Methods Within two weeks, twenty-one PAH patients (mean age: 54(15) years; mean pulmonary arterial pressure: 42(12) mmHg) completed two cycling exercise tests (incremental cardiopulmonary cycling exercise test (CPET) and CET) and three field tests (ISWT, ESWT and six-minute walk test (6MWT)). Physiological parameters were continuously monitored using the same portable telemetric device. Results Peak oxygen consumption (VO(2peak)) was similar amongst the five exercise tests (p = 0.90 by ANOVA). Walking distance correlated markedly with the VO(2peak) reached during field tests, especially when weight was taken into account. At 100% exercise, most physiological parameters were similar between incremental and endurance tests. However, the trends overtime differed. In the incremental tests, slopes for these parameters rose steadily over the entire duration of the tests, whereas in the endurance tests, slopes rose sharply from baseline to 25% of maximum exercise at which point they appeared far less steep until test end. Moreover, cycling exercise tests induced higher respiratory exchange ratio, ventilatory demand and enhanced leg fatigue measured subjectively and objectively. Conclusion Endurance tests induce a maximal physiological demand in PAH. Differences in peak respiratory response during exercise are related to the modality (cycling vs. walking) rather than the progression (endurance vs. incremental) of the exercise tests.